Transcriptional network analysis of human astrocytic endfoot genes reveals region-specific associations with dementia status and tau pathology - Simon, Matthew J.; Wang, Marie X.; Murchison, Charles F.; Roese, Natalie E.; Boespflug, Erin L.; Woltjer, Randall L.; Iliff, Jeffrey J. (Scientific reports, 2018)
The deposition of misfolded proteins, including amyloid beta plaques and neurofibrillary tangles is the histopathological hallmark of Alzheimer’s disease (AD). The glymphatic system, a brain-wide network of perivascular pathways that supports interstitial solute clearance, is dependent upon expression of the perivascular astroglial water channel aquaporin-4 (AQP4). Impairment of glymphatic function in the aging rodent brain is associated with reduced perivascular AQP4 localization, and in human subjects, reduced perivascular AQP4 localization is associated with AD diagnosis and pathology. Using human transcriptomic data, we demonstrate that expression of perivascular astroglial gene products dystroglycan ( DAG1 ), dystrobrevin ( DTNA ) and alpha-syntrophin ( SNTA1 ), are associated with dementia status and phosphorylated tau (P-tau) levels in temporal cortex. Gene correlation analysis reveals altered expression of a cluster of potential astrocytic endfoot components in human subjects with dementia, with increased expression associated with temporal cortical P-tau levels. The association between perivascular astroglial gene products, including DTNA and megalencephalic leukoencephalopathy with subcortical cysts 1 ( MLC1 ) with AD status was confirmed in a second human transcriptomic dataset and in human autopsy tissue by Western blot. This suggests changes in the astroglial endfoot domain may underlie vulnerability to protein aggregation in AD.